Majorca as a Translational Space: Creating and Questioning Identity through Translation - Mansell, Richard (Text Matters: A Journal of Literature, Theory and Culture, 2025)
Majorca offers a rare combination of opportunities to develop a study of translation and space. Not only is it a site of rich historical cultural contact, but it is also a present location of contact and tension: between Spanish and Catalan; between distinct forms of Catalan; with the languages spoken by significant economic migrant populations and expatriate communities, and languages represented by large tourist populations. Processes of layering, replacement, addition, and effacement of cultural forms are evident throughout the island, to the point that translation is a condition for creating Majorca’s own cultural identity. In this article I shall develop Sherry Simon’s search for translation in the urban environment to identify and analyse translational markers on the Mediterranean island of Majorca and its capital Palma, and seek their effects on the island’s communities as well as their sense of identity. I thereby propose “strong” forms of translation to complement the “weak” forms sketched by Simon. These strong forms result from cultural contact to ensure a deeper understanding of cultural identity, and empathy between cultures in our increasingly interconnected world.